Cover Image. (16th June 2021) - Traisrisilp, Kuntharee; Chankhunaphas, Wisit; Sirilert, Sirinart; Kuwutiyakorn, Varangtip; Tongsong, Theera
Abstract : The cover image is based on the Research Letter New genetic and clinical evidence associated with fetal Beckwith–Wiedemann syndrome by Kuntharee Traisrisilp et al., https://doi.org/10.1002/pd.5956 .